Collaborative Supervision and Evaluation of (Context, Input, Process and Product) in Muhadatsah Sobahiyah Program - Muhamad Muzaki Kurnia Ilahi; Wardiyatul Husna; Zakiyah Arifa; Nur Kholid; Halimatus Sa'diyah (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research is based on the importance of supervision and evaluation as part of the program management function. Supervision and evaluation of the program need to be carried out to measure its success and feasibility. The purpose of this study is to find out how the management supervision, and evaluation of the context, input, process and product model in muhadatsah sobahiyah program at Darussalam Gontor for Girls Islamic Boarding School 2. This study uses a qualitative approach with a descriptive type of research. All data is obtained through observation, Semi-structured interviews, and documentation techniques. Triangulation is performed to test the credibility of the data. Participants in this study consisted of 5 language supervisors, three of whom were members of the Language Advisory Council and two were members of the Central Language Improvement. The research results showed that the supervision process was carried out by the deputy caretaker, Language Advisory Council, Central Language Improvement, and the regional language section. Muhadatsah supervision at Gontor for Girls Campus 2 includes internal, repressive, preventive, active and passive supervision as well as formal truth supervision. It was also discovered that supervision of the program was carried out collaboratively. while the evaluation carried out on the program consists of 4 elements, namely context, process input, and product. So far, the muhadatsah program at Islamic Boarding School Darussalam Gontor for Girls Campus 2 has run according to expectations and desired goals. The advice for researchers can then continue research on supervision and evaluation of other learning programs in an institution. In addition, this research can be one of the references for academics in efforts to implement supervision and evaluation of programs, especially the Arabic language education program.